EARTHWORM POPULATION AT THE POST COAL MINING FIELD IN EAST KALIMANTAN, INDONESIA - Nugroho, Ardiyanto W.; Widuri, Septina A.; Sayektiningsih, T. (Association of Indonesian Forestry and Environment Researchers and Technicians, 2018)
Coal mining activities in Indonesia result in heavy soil degradation and significant decrease in earthworm population. This study aims to explore the population of earthworms at different ages of the plant in the post coal mining rehabilitation areas. PT. Kideco Jaya Agung, East Kalimantan. In this study, 5 samples (30 cm x 30 cm, 20 cm depth) of soil were collected from 5 rehabilitation sites. Sites were selected based on age after rehabilitation: 2, 4, 6, 8 and 10 years after replanting, and sampled with 20 m distances between samples to determine earthworm population. The depth of litter layer and species of plants were also recorded at each site. Chi square analysis was conducted to determine the significance of earthworm density in rehabilitation sites at different ages, while correlation analysis was conducted to determine correlation between litter thickness and the number of earthworms found in the research sites. Only 2 species of earthworms were found in this study; their abundance increased increased in line with the age of rehabilitation areas. The number of earthworms (density) at 10 years after rehabilitation was almost similar to that in the natural forests. In conclusion, planting tree species producing significant amount of litter might stimulate the earthworm community and initiate succession. It might also take more than 10 years to return to the previous state for the earthworms in terms of density after land rehabilitation of the coal mining areas is conducted.